UPAYA GURU DALAM PEMBENTUKAN AKHLAK SISWA MELALUI KEGIATAN EKSTRAKULIKULER BACA TULIS AL-QUR’AN DI MA NEGERI KOTA BATU - Ibrahim Maulana Syahid Nur A’la; M. Hanif; Ika Anggraheni (Al Hikmah: Jurnal Studi Keislaman, 2020)
Abstract: This study aims to find out 1) the form of al-Qur'an literary extracurricular activities in MA Negeri Kota Batu; 2) the implementation of students' moral formation through extracurricular reading and writing activities of al-Qur'an in MA Negeri Kota Batu; and 3) teacher's efforts in shaping student morals through al-Qur'an literary extracurricular activities at MA Negeri Kota Batu. To produce the results of his research, researchers used a descriptive qualitative approach and type of case study research. Data collection techniques carried out by interview, observation, and documentation. The results showed that: 1) the form of extracurricular reading and writing activities of al-Qur'an is divided into three levels, namely the levels of ula, wustho, and ulya; 2) the implementation of students 'moral formation through extracurricular reading and writing activities of al-Qur'an consists of: introduction, core, and closing, as well as being supported by the teacher providing motivation through inspirational stories, familiarizing students' acceptance before the learning process, and ending the learning process with advice relating to moral behavior; and 3) the teacher's efforts in shaping students' morals through al-Qur'an written and written extracurricular activities consist of teaching students to pray correctly and linking them with reading al-Qur'an; accustom students to read al-Qur'an at home in order to practice the mandate and responsibility for the tasks given; provide penalties for students who do not carry out extracurricular activities of reading and writing al-Qur'an well; be a good example for students in every action, speech, and behavior for their students to motivate students to improve the reading of al-Qur'an with diligence, enthusiasm, and continuously; and associate each reading of al-Qur'an studied with the stories of prophets, friends, scholars, or other figures. Keywords: Teacher, Morals, Extracurricular, al-Qur'an Read and Write